2023
DOI: 10.1183/16000617.0197-2022
|View full text |Cite
|
Sign up to set email alerts
|

Severe COVID-19versusmultisystem inflammatory syndrome: comparing two critical outcomes of SARS-CoV-2 infection

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is associated with diverse host response immunodynamics and variable inflammatory manifestations. Several immune-modulating risk factors can contribute to a more severe coronavirus disease 2019 (COVID-19) course with increased morbidity and mortality. The comparatively rare post-infectious multisystem inflammatory syndrome (MIS) can develop in formerly healthy individuals, with accelerated progression to life-threatening illness. A common t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 211 publications
0
2
0
Order By: Relevance
“…This was not the case with male versus female responses to SARS-CoV-2, as initially, severe COVID-19 was less likely in females, and male COVID-19+ individuals had higher rates of mortality in comparison to females [ 52 , 53 , 54 , 55 ]. Acute respiratory distress syndrome (ARDS) and sepsis were common in high-risk COVID-19+ individuals (predominantly male), highlighting a need to reprogram immunity towards a more productive anti-viral response [ 55 , 56 ] that prevents excess inflammation and improves adaptive immunity and T cell memory [ 13 , 14 , 57 ]. Disappointingly, when we evaluated biological sex variables in our analysis, we did not find clear statistical significance in our experimental outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This was not the case with male versus female responses to SARS-CoV-2, as initially, severe COVID-19 was less likely in females, and male COVID-19+ individuals had higher rates of mortality in comparison to females [ 52 , 53 , 54 , 55 ]. Acute respiratory distress syndrome (ARDS) and sepsis were common in high-risk COVID-19+ individuals (predominantly male), highlighting a need to reprogram immunity towards a more productive anti-viral response [ 55 , 56 ] that prevents excess inflammation and improves adaptive immunity and T cell memory [ 13 , 14 , 57 ]. Disappointingly, when we evaluated biological sex variables in our analysis, we did not find clear statistical significance in our experimental outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The causes underlying the delay and impairment of the acute virus-specific immune effectors in patients with severe and critical COVID-19 are poorly understood. Previous studies 28,29 revealed that aging and multiple comorbidities suppress early T cell responses and are associated with immunological aging. The present study also confirmed that age, gender, and coexisting disorders correlated with disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Согласно статистическим данным Всемирной организации здравоохранения, среди детей COVID-19 встречался менее чем у 2% [5]. Так, в Швейцарии заболеваемость детей до 10 лет cоставила 0,4%, 10-18 лет -2,6%, в Испании -0,8%, в Индии до 10 лет -2,5% и 10-18 лет -5%, в Китае -5,9%, в США -1,7% [5].…”
Section: Covid-19unclassified
“…Согласно статистическим данным Всемирной организации здравоохранения, среди детей COVID-19 встречался менее чем у 2% [5]. Так, в Швейцарии заболеваемость детей до 10 лет cоставила 0,4%, 10-18 лет -2,6%, в Испании -0,8%, в Индии до 10 лет -2,5% и 10-18 лет -5%, в Китае -5,9%, в США -1,7% [5]. Исходя из данных Федерального детского реанимационно-консультативного центра РФ, коронавирусной инфекцией переболели около 50 000 детей -6,6% (рис.…”
Section: Covid-19unclassified